1968
DOI: 10.1126/science.162.3860.1397
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber Sex Expression Modified by 2-Chloroethanephosphonic Acid

Abstract: Application of 2-chloroethanephosphonic acid (120 to 240 parts per million) to monoecious cucumber plants when the first true leaf was 2 centimeters in diameter has resulted in as many as 19 continuous pistillate nodes. Control of the flowering habit simplifies the production of hybrid seed and offers the possibility of enhancing cucumber yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 1 publication
7
43
0
Order By: Relevance
“…Treatment of cucumber plants with ethephon or with ethylene promoted the development of female flowers (McMurray and Miller 1968, Rudich et al 1969, Iwahori et al 1970. Inhibitors of both ethylene action and biosynthesis suppress female flower development (Beyer 1976, Atsmon andTabbak 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of cucumber plants with ethephon or with ethylene promoted the development of female flowers (McMurray and Miller 1968, Rudich et al 1969, Iwahori et al 1970. Inhibitors of both ethylene action and biosynthesis suppress female flower development (Beyer 1976, Atsmon andTabbak 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was found that Ethrel2, which releases ethylene in the presence of plant tissues (31), is remarkably effective in increasing femaleness in cucumber (14,16,24,25,30). The experiments reported here were initiated to study the effects of ethylene, Ethrel, gibberellins, growth retardants, and inhibitors on sex expression in cucumber.…”
Section: Introductionmentioning
confidence: 99%
“…Applied auxins, especially a-naphthaleneacetic acid, induce femaleness (8,13,15), whereas gibberellins induce maleness (8,23,27 Recently it was demonstrated that in some plant responses auxin may exert its effect through ethylene evolution (29) and that gibberellins have generally an opposing effect to ethylene (28). Since it has long been known that unsaturated hydrocarbons (17, 18,19) induce femaleness in cucumber, it appears that ethylene, the most potent unsaturated hydrocarbon affecting plants (4), may be the active factor for inducing femaleness.Recently it was found that Ethrel2, which releases ethylene in the presence of plant tissues (31), is remarkably effective in increasing femaleness in cucumber (14,16,24,25,30). The experiments reported here were initiated to study the effects of ethylene, Ethrel, gibberellins, growth retardants, and inhibitors on sex expression in cucumber.…”
mentioning
confidence: 99%
“…High endogenous auxin levels (2) are associated with female tendency, and exogenous auxin treatments (5) enhance the femaleness of cucumber plants, whereas high endogenous gibberellin levels are associated with maleness (1). Ethephon [(2-chloroethyl) phosphonic acid], which releases ethylene in plant tissues (11), also changes the sex expression of cucumbers, enhancing femaleness (6,10 Ethylene evolution was determined by gas chromatography using a Packard gas chromatograph equipped with a flame ionization detector and 36-X ¼-inch alumina column. Ethylene was determined in a 2-ml sample removed from a 30-or 100-ml vessel in which the tissue was incubated for 2 hr at 25 C at a light intensity of 600 ft-c.…”
mentioning
confidence: 99%